Modern issues of corrosive firmness of underground equipment complexes for mineral oil output - Djabbarov S. N. (Innovative technologies in science and education, 2016)
in this article the author analyzes the causes of corrosion failures of underground wells equipment while oil extraction and also considers the available measures to reduce the negative effects of corrosive influence.
Keywords: нефтепромысловое оборудование; электрохимическая коррозия; коррозионный процесс; ущерб от коррозии; химическая коррозия; защита комплексов; подземное оборудование; протекторная защита от коррозии; металлопластмассовые трубы; защитные полимерные покрытия; oilfield equipment; electrochemical corrosion; corrosion process; damage caused by corrosion; chemical corrosion; complex protection; underground equipment; protection defence from corrosion; metal-plastic pipes; protective polymer coatings